Eccentricity effect of micropatterned surface on contact angle - Kashaninejad, Navid (2012)
This article experimentally shows that the wetting property of a micropatterned surface is a function of the center-to-center offset distance between successive pillars in a column, referred to here as eccentricity. Studies were conducted on square micropatterns which were fabricated on a silicon wafer with pillar eccentricity ranging from 0 to 6 μm for two different pillar diameters and spacing. Measurement results of the static as well as the dynamic contact angles on these surfaces revealed that the contact angle decreases with increasing eccentricity and increasing relative spacing between the pillars. Furthermore, quantification of the contact angle hysteresis (CAH) shows that, for the case of lower pillar spacing, CAH could increase up to 41%, whereas for the case of higher pillar spacing, this increment was up to 35%, both corresponding to the maximum eccentricity of 6 μm. In general, the maximum obtainable hydrophobicity corresponds to micropillars with zero eccentricity. As the pillar relative spacing decreases, the effect of eccentricity on hydrophobicity becomes more pronounced. The dependence of the wettability conditions of the micropatterned surface on the pillar eccentricity is attributed to the contact line deformation resulting from the changed orientation of the pillars. This finding provides additional insights in design and fabrication of efficient micropatterned surfaces with controlled wetting properties.